The Sociological Imagination within Teaching Sociology: 1973–2020. (January 2023) - Palmer, Nathan
The sociological imagination is widely considered essential to sociology and sociological scholarship-of-teaching-and-learning research. Still, sociologists have struggled to agree on precisely what it is and how to measure its development effectively. A content analysis of every article published in Teaching Sociology was conducted examining where the sociological imagination appeared in the journal, where authors claimed to develop students' sociological imagination, and the methodological sophistication of the evidence they provided to substantiate those claims. Analysis confirms the importance of the sociological imagination, appearing in a fourth of all published articles and nearly half of the articles published between 2010 and 2020. Just over a fourth of claims-making authors provided no evidence to validate their claims, and the frequency of making unsubstantiated claims persists even as the methodological rigor of the journal overall increased. Among the studies that provided evidence, however, the methodological sophistication appears to be increasing.